United Kingdom National Ophthalmology Database Study: Diabetic Retinopathy; Report 1: prevalence of centre-involving diabetic macular oedema and other grades of maculopathy and retinopathy in hospital eye services. - Keenan, T D L; Johnston, R L; Donachie, P H J; Sparrow, J M; Stratton, I M; Scanlon, P (Eye (0950-222X), 2013)
Aims: To report estimates of the prevalence of diabetic retinopathy (DR) and maculopathy grades for a large cohort of patients managed by the UK hospital eye service (HES).Methods: Anonymised data were extracted from 30 UK NHS hospital trusts using a single ophthalmic electronic medical record (EMR) for the period from April 2000 to November 2010 to create the National Ophthalmology Database (NOD). From 2007, the EMR facilitated capture of a nationally agreed-upon standardised data set (DR Structured Assessment) relating to the presence or absence of clinical signs of DR and maculopathy. An algorithm in the software automatically calculated the Early Treatment of Diabetic Retinopathy Study grades of retinopathy and maculopathy.Results: Between 2007 and 2010, 307,538 patients had data on the NOD, with 76,127 (24.8%) patients having been recorded as having diabetes. The proportion of patients with diabetes who had a structured assessment increased from 50.7% (2007) to 86.8% (2010). In each NHS year, 12.6-20.6% of eyes with structured assessments had no DR; 59.6-67.3% had non-proliferative DR; and 18.3-20.9% had active or regressed proliferative DR. Clinically significant macular oedema was present in 15.8-18.1% of eyes, and in 8.7-10.0% of eyes, this involved the central macula.Conclusion: This study provides contemporary estimates of the prevalence of retinopathy and maculopathy grades in a large cohort of patients with diabetes managed by the UK HES. Centre-involving diabetic macular oedema, potentially amenable to anti-VEGF therapy, is present in the eyes of almost 10% of these patients. This information is useful for clinicians, health-care economists, and commissioners involved in planning and delivering diabetic eye services.